Hsp40 Protein LeDnaJ07 Enhances the Thermotolerance of Lentinula edodes and Regulates IAA Biosynthesis by Interacting LetrpE - Wang, Gangzheng; Luo, Yi; Wang, Chen; Zhou, Yan; Mou, Chunye; Kang, Heng; Xiao, Yang; Bian, Yinbing; Gong, Yu Hua (Frontiers in Microbiology, 2020)
Our previous study found that LeDnaJ07 RNAi decreased Lentinula edodes resistance to heat stress and Trichoderma atroviride infection. In this study, the structure and function of the LeDnaJ07 gene was analyzed by gene cloning and overexpression in L. edodes stress-sensitive strain YS55 via the Agrobacterium-mediated transformation method. Transformants were confirmed by qRT-PCR, fluorescence observation and Southern blotting. Overexpression of LeDnaJ07 in YS55 not only enhanced L. edodes mycelial resistance to heat stress but also facilitated mycelial growth. In the presence of heat stress, the intracellular IAA content showed a significant increase in the two LeDnaJ07 overexpression strains but only a slight change in the YS55 wild type strain. Moreover, the interaction between LeDnaJ07 and LetrpE was demonstrated via Y2H and BiFC assays. These results suggested that LeDnaJ07 may be involved in regulating IAA biosynthesis and the resistance of L. edodes to heat stresses via interacting with LetrpE.